2014
DOI: 10.1371/journal.pmed.1001605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water, Sanitation, and Hygiene on the Prevention of Trachoma: A Systematic Review and Meta-Analysis

Abstract: Matthew Freeman and colleagues identified 86 individual studies that reported a measure of the effect of water, sanitation, and hygiene on trachoma and conducted 15 meta-analyses for specific exposure-outcome pairs. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(184 citation statements)
references
References 94 publications
7
173
2
2
Order By: Relevance
“…These results are in contrast with systematic reviews that have reported significant health gains from rural household sanitation interventions (Esrey et al 1991;Wolf et al 2014;Clasen et al 2010;Engell & Lim 2013;Ziegelbauer et al 2012;Stocks et al 2014;Strunz et al 2014). They are consistent, however, with another trial of a sanitation project implemented within the context of the TSC in the state of Madhya Pradesh (Patil et al 2014).…”
Section: Discussioncontrasting
confidence: 52%
“…These results are in contrast with systematic reviews that have reported significant health gains from rural household sanitation interventions (Esrey et al 1991;Wolf et al 2014;Clasen et al 2010;Engell & Lim 2013;Ziegelbauer et al 2012;Stocks et al 2014;Strunz et al 2014). They are consistent, however, with another trial of a sanitation project implemented within the context of the TSC in the state of Madhya Pradesh (Patil et al 2014).…”
Section: Discussioncontrasting
confidence: 52%
“…Trachoma has been linked with low levels of sanitation 31 and we noted very low levels of sanitation in all EUs other than NCD. Less than 0.1% of households in the Southern Highlands had improved sanitation.…”
Section: Discussionmentioning
confidence: 54%
“…ITI collaborates with governmental and nongovernmental organizations at the local, national and international levels to implement SAFE strategy for trachoma control 23, 24, 25, 26, 27…”
Section: Management and Preventionmentioning
confidence: 99%